Analysis of bibliometrics in studying the influence of the environment on preschool children’s psychological development - Thi Ut Sau, Nguyen; Thi Nhung, Tran; Kieu Oanh, Pham Thi; Thi Thuy, Vu; Thuong Thuong, Le Thi; Thi Hoa, Nguyen (Institute of Advanced Engineering and Science, 2025)
This article aims to provide an overall picture of research on the environment’s influence on preschool children’s psychological development. The researchers used the preferred reporting items for systematic reviews and meta-analysis (PRISMA) method to collect data and VOSviewer software to analyze 119 articles from the Scopus database from 2000 to 2023. The results showed that since 2006, i) the environmental influence on the psychological development of preschool children has received much attention; ii) the United States and the United Kingdom are the two leading countries in terms of the number of publications; iii) Leve, Neiderhiser, Reiss, and Shaw are the four leading authors; iv) 16 out of 20 influential journals in this field are Q1 journals, most of which belong to educational psychology. The two main concerns of the authors in these 119 articles are “parenting” and “development.” In the past five years, researchers have focused on topics such as “autism,” “preschoolers,” “environment,” “COVID-19”, and “externalizing problems”.